1999
DOI: 10.1093/ps/78.10.1443
|View full text |Cite
|
Sign up to set email alerts
|

Venous blood pressure in broilers during acute inhalation of five percent carbon dioxide or unilateral pulmonary artery occlusion

Abstract: We evaluated the hypothesis that venous congestion (increased venous volume), as reflected by venous hypertension (increased venous pressure), can arise when the right ventricle is unable to elevate the pulmonary arterial pressure sufficiently to propel the cardiac output through an anatomically inadequate or inappropriately constricted pulmonary vasculature. Changes in venous pressure were evaluated in clinically healthy broilers during modest increases in pulmonary vascular resistance induced by inhalation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…High mean paCO 2 (higher than 60 mm Hg) and low pH and paO 2 values in arterial blood of sire lines differed at wk 5 highly significant (P< 0.001) from values found in dam lines and in BC birds. Wideman et al (1999) demonstrated that even a short period of 5 minutes of a modest increase in partial pressure of CO 2 (up to 55 mm Hg) together with a reduced pH in arterial blood of broilers was sufficient to trigger a significant increase in pulmonary arterial pressure, predisposing the birds to ascites. Reeves et al (1990) discovered that at sea level, ascites susceptible chickens have impaired ventilatory drives and that they have relative hypoventilation at an early age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High mean paCO 2 (higher than 60 mm Hg) and low pH and paO 2 values in arterial blood of sire lines differed at wk 5 highly significant (P< 0.001) from values found in dam lines and in BC birds. Wideman et al (1999) demonstrated that even a short period of 5 minutes of a modest increase in partial pressure of CO 2 (up to 55 mm Hg) together with a reduced pH in arterial blood of broilers was sufficient to trigger a significant increase in pulmonary arterial pressure, predisposing the birds to ascites. Reeves et al (1990) discovered that at sea level, ascites susceptible chickens have impaired ventilatory drives and that they have relative hypoventilation at an early age.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Wideman et al (1999) in broilers showed that a moderate increase in CO 2 concentrations of arterial blood (up to 55 mm Hg) in concert with a decreased pH, by inhalation of 5% CO 2 , clearly increased pulmonary arterial pressure. Birds with those increased arterial CO 2 values are apparently predisposed to ascites.…”
Section: Introductionmentioning
confidence: 99%
“…However, such an increase, if not coupled to plasma volume expansion would increase blood viscosity, followed by increased bloodflow resistance [90]. The back pressure in the veins causes venous congestion, dilation and prominent vessels [50]. The lack of O2 in the heart muscle results in hypoxic damage and, finally, right-ventricular hypertrophy.…”
Section: Ascites Physiology and Etiologymentioning
confidence: 99%
“…Several significant alterations to the blood system in AS broilers were well documented: increased red blood cell numbers, through increased erythropoietin production [96,100,[150][151][152][153]; elevation of hematocrit values and blood viscosity [54,72,154], and central venous blood congestion [50,155]. These findings raised the question of the association between the plasma and the fluid that accumulated in the abdominal cavity, and whether the increase in hematocrit resulted from a decline in plasma volume caused by plasma leakage out of the blood vessels, or from increased erythropoiesis that occurred as a compensatory reaction to the lack of oxygen in the tissue.…”
Section: Blood O2 Transport Erythropoiesis and Ascitesmentioning
confidence: 99%
See 1 more Smart Citation